Biosynthesis of the Peptide Antibiotic Feglymycin by a Linear Nonribosomal Peptide Synthetase Mechanism. Issue 18 (30th October 2015) - Gonsior, Melanie; Mühlenweg, Agnes; Tietzmann, Marcel; Rausch, Saskia; Poch, Annette; Süssmuth, Roderich D.
Abstract: Feglymycin, a peptide antibiotic produced by Streptomyces sp . DSM 11171, consists mostly of nonproteinogenic phenylglycine‐type amino acids. It possesses antibacterial activity against methicillin‐resistant Staphylococcus aureus strains and antiviral activity against HIV. Inhibition of the early steps of bacterial peptidoglycan synthesis indicated a mode of action different from those of other peptide antibiotics. Here we describe the identification and assignment of the feglymycin ( feg ) biosynthesis gene cluster, which codes for a 13‐module nonribosomal peptide synthetase (NRPS) system. Inactivation of an NRPS gene and supplementation of a hydroxymandelate oxidase mutant with the amino acidl ‐Hpg proved the identity of the feg cluster. Feeding of Hpg‐related unnatural amino acids was not successful. This characterization of the feg cluster is an important step to understanding the biosynthesis of this potent antibacterial peptide. Abstract : Feglymycin, a phenylglycine‐rich peptide antibiotic, has a very rare mode of action. Sequencing has revealed a putative feglymycin gene cluster in Streptomyces sp. DSM 11171. Here we describe inactivation mutants and rescue experiments that validated the authenticity of the cluster.